#### Answer

-1$\frac{1}{3}$

#### Work Step by Step

$\frac{4}{3}$-$\frac{8}{3}$=$\frac{4-8}{3}$=
$\frac{-4}{3}$=
-1$\frac{1}{3}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

-1$\frac{1}{3}$

$\frac{4}{3}$-$\frac{8}{3}$=$\frac{4-8}{3}$=
$\frac{-4}{3}$=
-1$\frac{1}{3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.